2022
DOI: 10.3390/jof8030287
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics, Antifungal Susceptibility, and MLST-Based Genetic Analysis of Cryptococcus Isolates in Southern Taiwan in 2013–2020

Abstract: Cryptococcal meningoencephalitis (CM) is a treatable condition, but it leads to excessive morbidity and mortality. We collected 115 non-duplicated Cryptococcus clinical isolates during 2013–2020 in southern Taiwan to perform antifungal susceptibility testing. Multi-locus sequence typing was performed on 96 strains from patients with CM (n = 47) or cryptococcemia (n = 49). In addition, the epidemiological and clinical characteristics of patients with CM during 2013–2020 (n = 47) were compared with those during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…MLST has revealed geographical associations with clonal populations with increased heterogeneity possibly related to the origins of the species; for example, C. gattii , may have spread from Australia and Northern Brazil to North America and Canada [ 28 , 29 ] whereas for C. neoformans, ST5 is the predominant serotype in China and Taiwan, ST93 in Brazil, ST41 in Japan and the US, with greater diversity in African countries [ 16 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Latest On Taxonomy and Molecular Epidemiology Of Cryptococcusmentioning
confidence: 99%
“…MLST has revealed geographical associations with clonal populations with increased heterogeneity possibly related to the origins of the species; for example, C. gattii , may have spread from Australia and Northern Brazil to North America and Canada [ 28 , 29 ] whereas for C. neoformans, ST5 is the predominant serotype in China and Taiwan, ST93 in Brazil, ST41 in Japan and the US, with greater diversity in African countries [ 16 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Latest On Taxonomy and Molecular Epidemiology Of Cryptococcusmentioning
confidence: 99%
“…We identified the organism as C. gattii ; its score value was 1.92 by Bruker Biotyper matrix-assisted laser desorption/ionization time-of-flight mass spectrometry system (Bruker Daltonics GmbH, https://www.bruker.com ). We performed multilocus sequence typing (MLST) and phylogenetic analysis MLST for 7 genetic loci, including CAP59 , GPD1 , IGS1, LAC1 , PLB1 , SOD1 , and the URA5 region, as previously described ( 2 ), and detected C. gattii ST576. We deposited sequence data of the 7 foci from MLST into GenBank (accession nos.…”
mentioning
confidence: 99%
“…OP828681–87). The URA5 gene restriction fragment length polymorphism of the C. gattii isolate performed as previously described ( 3 ); the results showed that this isolate belonged to the VGIV genotype, C. tetragattii (CMU-3028) ( 2 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…grubii isolated from patients and pigeon droppings in Asia are ST 4, 5, 6, and 93 [ 13 ]. ST 31 is relatively rare in humans in Taiwan and Asian areas [ 5 , 13 ]. The only reference of cats infected by ST 31 manifests as nasal or facial masses and ulcers but without involving the CNS [ 14 ].…”
mentioning
confidence: 99%